Influence of Profitability, Tax Aggressiveness, and Institutional Ownership of Corporate Value - Eva Fadhilah; Syaiful Syaiful; Nyimas Wardatul Afiqoh (INNOVATION RESEARCH JOURNAL, 2020)
The research aimed to determine the effect of profitability, tax aggressiveness, and institutional ownership to the firm value. This research was used a casual method by taking secondary data. The selection of sample used purposive sampling method. From the predetermined criteria obtained a sample of 43 companies with study period of 2015-2017, so total of observation is 129. Analyzing of data was used multiple linear regression analyzed. The results shows that the profitability and tax aggressiveness have influence to the firm value. But the institutional ownership does not have influence to the firm value.